A justiça do trabalho no governo de Getúlio Vargas e suas peculiaridades estruturais: análise das reclamações trabalhistas da junta de conciliação e julgamento de Fortaleza (1941-1946) - Meireles Júnior, Cláudio Alcântara (2021)
The objective of this research was to investigate the installation of the Labor Justice in the government of Getúlio Vargas, in order to understand the genesis of its original structure, its peculiar characteristics and how it s concret e functioning occurred in the first years of operation T he workers were considered the protag onists of the law suits and th e main focus was on the Fortaleza s local reality . It was considered essential to revisit the Vargas period in order to unde rstand th e foundation of the b razilian Social State, revealing fallacious inferences about the ideologi cal matrix of the work er protection apparatus in Brazil, focusing on the installation, functioning and operation of the Labor Justice in Brazil in the 19 40s. In o rder to fulfill these purposes , as for the methodological aspects , the law studies are a histo rical form of knowledg e connected with the political ideals of the period . Furthe rmore, the category of cultural translation was very important to understand the possible infl uences of t he anti liberal conceptions in the legislation of the Vargas administration, especially the corporatism premisses . The research was divided in to four c hapters with the following purposes: 1) Study of the b razilian Social State under an authorit arian regime, examining corporatism as a third way proposal and its creative appropriation by Oliveira Vianna; (2) Description of the normative evolution of the L abor Justice regulation , with the intention of understanding their peculiarities 3) O utline t he l abor context in Fortaleza Ceará in the 1940s , a peripheral loca tion compared to the country's major economic centers of industrialization ; (4) Analys is of the labor lawsuit s filed bet ween 1941 and 1946 in the Fortaleza s Labor Court , aiming to clarify how the specialized justice functioned concretely based on the workers' actions as subjects of rights. It was concluded that the theory of the copy of th e fascist L abor B ill of R ights Carta del Lavoro must be discarded, as a consequence of t he premises of cultural translatio n and globol circulation of ideas; the Labor Court played an important role in the ideological scope of denying class c onflict t heories the making of the subjects of labor law took place not only through the social legisl ation, but especially by t he individualized action of the workers in lawsuits, gradually building the b razilian work er's identity.